(untitled) (Bodhi Path, 2022)
The present work is a humble attempt to explore the experiential nature of reality in Buddhism through a brief analysis of the views of reality expounded by different Buddhist schools, particularly the early Buddhism, Yogacara, and the Madhyamaka. Reality in early Buddhism is the passing phenomena with no underlying essence yet connected by a causal principle. Understanding it and getting rid of the tendency of mistaking ephemeral things for eternal is Nirvana. For the Yogācāra, reality is cittamātra that denies the existence of any worldly phenomena outside consciousness. The Mādhyamaka śūnyavāda espouses the intrinsic emptiness of all phenomena— mental and physical. Finally, the paper tries to establish that in the Buddhist enterprise of reality, there is hardly any space between reality and experiencing reality. Hence the attempt to describe reality through language seems futile. Under the veil of differences in adopting methods and thus using different words/languages to delineate reality, there seems an unuttered consensus among the Buddhist thinkers regarding the notion that reality is experiential.